The 58th Cysteine of TcpP Is Essential for Vibrio cholerae Virulence Factor Production and Pathogenesis - Shi, Mengting; Li, Na; Xue, Yuanyuan; Zhong, Zengtao; Yang, Menghua (Frontiers in Microbiology, 2020)
Vibrio cholerae, the causative agent of the severe diarrheal disease cholera, has evolved signal transduction systems to control the expression of virulence determinants. It was previously shown that two cysteine residues in the periplasmic domain of TcpP are important for TcpP dimerization and activation of virulence gene expression by responding to environmental signals in the small intestine such as bile salts. In the cytoplasmic domain of TcpP, there are another four cysteine residues, C19, C51, C58 and C124. In this study, the functions of these four cysteine residues were investigated and we found that only C58 is essential for TcpP dimerization and for activating virulence gene expression. To better characterize this cysteine residue, site-directed mutagenesis was performed to assess the effects on TcpP homodimerization and virulence gene activation. A TcpPC58S mutant was unable to form homodimers and activate virulence gene expression, and did not colonize infant mice. However, a TcpPC19/51/124S mutant was not attenuated for virulence. These results suggest that C58 of TcpP is indispensable for TcpP function and is essential for Vibrio cholerae virulence factor production and pathogenesis.